Golden lion [compact disc, unabridged] : a novel of heroes in a time of war - Smith, Wilbur A. (Smith, Wilbur A. Courtney series., 2015)
Hal Courtney has always lived at sea. Now a truce has been made between the warring countries and Hal is captain of his own ship; the Golden Bough. From the slave markets of Zanzibar to the pirate-riddled waters of the Indian Ocean, Hal leads his crew in and out of the waves of danger. But he soon realizes that just because the war is over, does not mean the battle is won, and the more a man achieves, the more he has to lose.